Anatomical Study of the Hepatic Veins in Segment 4 of the Liver Using Three-Dimensional Visualization - Zhang, Jun; Guo, Xiaochao; Qiao, Qilu; Zhao, Jianxun; Wang, Xin (Frontiers in Surgery, 2021)
Objective: The current study aimed to examine the anatomical structure of the hepatic vein of segment IV liver (S4) of the liver using three-dimensional (3D) visualization technology in order to explore the surgical value of the middle hepatic vein (MHV) manipulation and highlight the importance of current research in hepatic surgery. Methods: Between January 2014 and December 2019, 52 patients with abdominal diseases(not including hepatic disease) were selected for multiphasic computed tomography-enhanced scans of the upper abdomen. A 3D visualization system was utilized to display the structural details of the hepatic veins in S4 of their livers. Couinaud’s eight-segment classification system was used to denote the liver’ sections. Results: The constructed 3D model clearly displayed vascular morphological characteristics and their location in the liver, hepatic artery and vein system, and portal vein system. Of the 52 patients, 43 had an umbilical fissure vein (UFV) (82.7%), 19 had an accessory S4 liver vein (36.5%), 16 had both a UFV (30.8%) and an accessory S4 liver vein, and 6 had neither (11.5%). A total of 79% of the patients with a UFV and 74.2% of those with an accessory S4 liver vein had venous blood returning into the left hepatic vein. Conclusion: 3D visualization technology was used to determine hepatic venous return of S4 hepatic veins and was found to improve the safety of evaluation in hepatic surgery.